Safety and Well-Being of Socially Vulnerable Children - Semya, G.V. (Psihologiâ i pravo, 2023)
The focus is on psychological and legal aspects of the well-being and safety of children who are socially vulnerable, including: children who are victims of violence and abuse; children separated from their parents due to the deprivation of parental rights; young people who are graduates of organizations for orphans and foster families; and children living in the territory of military conflicts. В фокусе внимания психологические и правовые аспекты благополучия и безопасности детей, относящихся к категории социально уязвимых: дети - жертвы насилия и жестокого обращения; дети, разлученные с родителями вследствие лишения их родителей родительских прав; молодые люди - выпускники организаций для детей-сирот и замещающих семей; дети, проживающие на территории военных конфликтов.